Patterns of live music promotion and management in Zimbabwe - Mhiripiri, Joyce Tsitsi (Routledge, 2021)
Music management and promotion in Zimbabwe are evolving as big business in the live music industry, with some notable personalities who are nearly as recognizable as the musicians and artists they manage or sponsor. Also evolving are systems of management, which can be critiqued using management concepts and methodologies. This paper applies normative management theories, with emphasis on Ubuntu management to the work of managing and promoting musicians. The roles of managers and promoters in the live music industry are examined to determine patterns of music promotion and management in Zimbabwe. The Zimbabwe live music industry is heavily dominated by Harare-based artists and venues to the extent that Harare sets the pace for the rest of the nation in terms of innovations in the relationship between musician and promoter or artist. The major concerns between musicians and their intermediaries were identified as: trust issues, ambition versus capacity, marketing lapses and administrative flaws, with the majority of players in the music industry being preoccupied with trust issues. Trust issues associated with breach of sponsor-musician or manager-musician contracts are so common in the Zimbabwean music industry that normative management principles ought to be encouraged for all involved.